2018
DOI: 10.3389/fphar.2018.00147
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A Upregulates Nrf2 Antioxidant Pathway and Thereby Alleviates Acetaminophen-Induced Hepatotoxicity

Abstract: Acetaminophen (APAP) overdose-induced fatal hepatotoxicity is majorly characterized by overwhelmingly increased oxidative stress while enhanced nuclear factor-erythroid 2-related factor 2 (Nrf2) is involved in prevention of hepatotoxicity. Although Licochalcone A (Lico A) upregulates Nrf2 signaling pathway against oxidative stress-triggered cell injury, whether it could protect from APAP-induced hepatotoxicity by directly inducing Nrf2 activation is still poorly elucidated. This study aims to explore the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 44 publications
(53 reference statements)
2
46
0
Order By: Relevance
“…Keap1 is a negative regulator of the transcription factor Nrf2, which mediated the inactivation of Nrf2 and thus enhanced Nrf2 translocation into the nucleus ( Satoh et al, 2006 ; Lv et al, 2018 ). It has been reported that protein p62, which is on the upstream of Nrf2 pathway, can inactivate Keap1 and activate Nrf2 ( Komatsu et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Keap1 is a negative regulator of the transcription factor Nrf2, which mediated the inactivation of Nrf2 and thus enhanced Nrf2 translocation into the nucleus ( Satoh et al, 2006 ; Lv et al, 2018 ). It has been reported that protein p62, which is on the upstream of Nrf2 pathway, can inactivate Keap1 and activate Nrf2 ( Komatsu et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Natural products have made enormous contributions to drug discovery, as they have many advantages over conventional chemical compound-based medications, such as fewer side effects, less long-term toxicity, and variable bioavailability and biological activity ( Kim, 2018 ). In recent years, intensive studies have demonstrated the protective effects of natural products against APAP-induced hepatotoxicity due to their multiple mechanisms of action in inflammation, oxidant/antioxidant balance and damage responses ( Ko et al, 2017 ; Lv et al, 2018 ). Iso (or homoorientin) is a chemical flavonoid-like compound that has been shown to exert anti-inflammatory effects and exhibit antioxidant potential ( Ye et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress causes injury in cells by generating reactive oxygen species (ROS), and excessive ROS in the liver can cause extensive liver injury ( Chan et al, 2006 ). Based on the significant pathophysiological role of antioxidation/detoxification system dysfunction in the development of liver diseases, antioxidant agents can be an effective strategy for fighting oxidative stress that causes liver damage and diseases ( Lv et al, 2018 ). Therefore, the ability of Iso to act as an antioxidant with anti-inflammatory activity renders this compound a prime candidate to be a hepatoprotective agent.…”
Section: Introductionmentioning
confidence: 99%
“…At therapeutic doses, APAP is mainly metabolized to nontoxic water-soluble metabolites by glucuronidation and sulfation in the liver, and only a small fraction of APAP is metabolized by various cytochrome P450s (CYPs) such as CYP2E1, CYP3A4, CYP1A2, and CYP1A1 to a toxic active product, N -acetyl-p-benzoquinoneimine (NAPQI) [4,5]. NAPQI forms APAP-glutathione, APAP-cysteine, and APAP- N -acetylcysteine by conjugating with glutathione (GSH) [6]. However, an APAP overdose exhausts glucuronidation and sulfation pathways and produces excess NAPQI, subsequently consuming GSH excessively.…”
Section: Introductionmentioning
confidence: 99%